An efficient constraint handling approach for economic load dispatch problem with non-smooth cost function - Abdullah, Mohd Noor (2015)
Increasing of the power demand and fuel cost in power generation required an advanced algorithm for scheduling the output of generating unit in economical manner. The economic load dispatch problem (ELD) problem consists several operational and system constraints such as prohibited operating zones (POZs) and ramp-rate limit need to handle wisely by optimization algorithm. Previously, the penalty function is widely used to satisfy the power balance and other constraints by augmenting the objective function with the penalized function. However, it required a proper penalty factor tuning and depends on the size of problem. This paper proposes an efficient constraint handling based on the repairing or adjusting infeasible solution into feasible solution in every iterative process. The simulation results show that the proposed constraints handling approach is better than penalty function approach in term of convergence characteristic and robustness